Revealing molecular orbital gating by transition voltage spectroscopy - Bâldea, Ioan (Chemical physics, 2010)
Recently, Song et al. [Nature 462, 1039 (2009)] employed transition voltage spectroscopy to demonstrate that the energy εH of the highest occupied molecular orbital (HOMO) of single-molecule transistors can be controlled by a gate potential VG. To demonstrate the linear dependence εH−VG, the experimental data have been interpreted by modeling the molecule as an energy barrier spanning the spatial source-drain region of molecular junctions. Since, as shown in this work, that crude model cannot quantitatively describe the measured I-V-characteristics, it is important to get further support for the linear dependence of εH on VG. The results presented here, which have been obtained within a model of a point-like molecule, confirm this linear dependence. Because the two models rely upon complementary descriptions, the present results indicate that the interpretation of the experimental results as evidence for a gate controlled HOMO is sufficiently general.